2008
DOI: 10.1186/1744-8069-4-52
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Gabapentin Analgesia in an Experimental Mouse Model of Fibromyalgia

Abstract: In a new mouse model for generalized pain syndrome, including fibromyalgia, which used intermittent cold stress (ICS), bilateral allodynia in the hindpaw was observed that lasted more than 12 days; thermal hyperalgesia lasted 15 days. During constant cold stress (CCS), mice showed only a transient allodynia. A female prevalence in ICS-induced allodynia was observed in gonadectomized but not in gonad intact mice. Systemic gabapentin showed complete anti-allodynic effects in the ICS model at the one-tenth dose f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
112
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(121 citation statements)
references
References 23 publications
7
112
2
Order By: Relevance
“…(Garry et al, 2005;Cheng and Chiou, 2006;Arnold et al, 2007;Dworkin et al, 2007;Gilron et al, 2007;Nishiyori et al, 2008). The mechanism of the analgesic action of gabapentin is still not clear but the recent reports proposed that gabapentin might act on several receptors and ion channels expressed in the dorsal root ganglia (DRG) or in the spinal cord dorsal horn neurons (Luo et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…(Garry et al, 2005;Cheng and Chiou, 2006;Arnold et al, 2007;Dworkin et al, 2007;Gilron et al, 2007;Nishiyori et al, 2008). The mechanism of the analgesic action of gabapentin is still not clear but the recent reports proposed that gabapentin might act on several receptors and ion channels expressed in the dorsal root ganglia (DRG) or in the spinal cord dorsal horn neurons (Luo et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In mice, the effective dose for relieving hyperalgesia in the repeated cold stress model was over three times smaller than that for reducing nerve injury-induced neuropathic pain, despite the effective dose of pregabalin being similar between fibromyalgia and neuropathic pain patients in a clinical setting (Dworkin et al, 2007;. Further, intracerebroventricular administration of gabapentin significantly attenuated hyperalgesia in the repeated cold stress model but not in the neuropathic pain model, possibly because up-regulation of the α2δ1 subunit may underlie the mechanism for repeated cold stress-induced hyperalgesia (Nishiyori and Ueda, 2008). No clear evidence has yet been presented that opiate drugs are effective in reducing pain in fibromyalgia patients, as no randomized controlled double blind clinical trial on opiates has been conducted with a sufficient number of fibromyalgia patients (Clauw, 2009).…”
Section: Predictive Validitymentioning
confidence: 94%
“…A nociception test is then conducted at room temperature at least 1 h after the end of stress exposure. Nishiyori and Ueda (2008) found that mice exhibited thermal hyperalgesia (reduction in paw withdrawal latency in response to thermal stimulation) and mechanical hyperalgesia (reduction in threshold for paw withdrawal in response to mechanical stimulation by the von Frey apparatus) for more than 12 days following the repeated cold stress. In contrast, mice exposed to constant cold temperature (4C) stress manifest only short-lasting hyperalgesia.…”
Section: Repeated Cold Stress Model 511 Methodsmentioning
confidence: 99%
See 2 more Smart Citations